2003
DOI: 10.1063/1.1573737
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry of thin film and bulk anatase (TiO2)

Abstract: Spectroscopic ellipsometry (SE) measurements were made on thin-film and single-crystal TiO2 anatase using a two-modulator generalized ellipsometer. The TiO2 films were epitaxially stabilized on a LaAlO3 substrate in the anatase crystal structure using reactive sputter deposition. The films were highly crystalline, possessing a “stepped surface” morphology indicative of atomic layer-by-layer growth. The SE results for the anatase film indicate that the material is essentially oriented with the c axis perpendicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
160
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(174 citation statements)
references
References 36 publications
13
160
0
Order By: Relevance
“…The k curves of the 300 C deposited TiO 2 showed two explicit peaks at about 3.96 and 4.56 eV, which were identical to the bulk anatase. 25 On contrary, a much smoother saturated ramp, instead of any clear peaks, could be found for the 120 C deposited amorphous TiO 2 . Therefore, it could be concluded that the shapes and positions of the corresponding refractive index curves differentiated with the crystalline phase.…”
Section: B Deposition Rate and Optical Propertiesmentioning
confidence: 93%
“…The k curves of the 300 C deposited TiO 2 showed two explicit peaks at about 3.96 and 4.56 eV, which were identical to the bulk anatase. 25 On contrary, a much smoother saturated ramp, instead of any clear peaks, could be found for the 120 C deposited amorphous TiO 2 . Therefore, it could be concluded that the shapes and positions of the corresponding refractive index curves differentiated with the crystalline phase.…”
Section: B Deposition Rate and Optical Propertiesmentioning
confidence: 93%
“…The extracted indices of the refraction (n) and the extinction coefficient (k) of the upper and lower layers as functions of wavelength are shown in Figure 4. The refractive index of the lower layer closes to the refractive index of the anatase TiO2 [35]. The upper layer shows a lower value of the refractive index and a larger value of the extinction coefficient because of its amorphous phase.…”
Section: Characterization Of Ald Tio 2 Thin Filmsmentioning
confidence: 95%
“…The index of anatase is considerably below that of rutile, and tables are not readily available. The many papers on the subject do not present consistent results [42][43][44][45][46]. For example, Dakka et al [42] show different indices for "new target" (NT) and "used target"…”
Section: E Index Of Titanium Dioxidementioning
confidence: 99%